Urząd subdiakonatu jako święcenie wyższe. Perspektywa historyczno-prawna rozwoju święceń subdiakonatu do XIII w. - Makowski, Dawid (Warszawskie Studia Teologiczne, 2024)
The article presents the origin and evolution of subdiaconate ordinations from the 3rd to the 13th century, using the historical-legal method. On the basis of the sources available today, an attempt was made to show the development of the former fifth degree of ordination, which as the only lower office of the Church in history became a higher one. To this end, the first part of the publication shows its formation and clericalization, carried out at the turn of antiquity and the Middle Ages. Then, a slow but decisive way of emphasizing the value of the office of subdeacons, which took place between the 6th and 10th centuries, was presented. The third part attempts to present a possible date for this reclassification. An analysis of the history of the subdiaconate helps to discern the nature of the former minor ordinations, so that all reforms concerning the present-day services of the lectorate and acolate, which are the only remnants of the former minor ordinations and the subdiaconate, can become more comprehensible.